Negotiations & bargaining: styles & stages - Craver, Charles B. (Henry Stewart Talks, 2011)
Personal styles affect bargaining interactions, Cooperative style, Competitive style, Hybrid competitive/cooperative style, Negotiation stages, Preparation stage (establishing limits & goals), Preliminary stage (establishing rapport with other Side), Information stage (value creation), Distributive stage (value claiming), Closing stage (value solidifying), Cooperative stage (value maximizing)
Reviewed at 2018/06/27